Preventive Approaches in Women's Neurology: Prepartum, Pregnancy, and Postpartum - Kirkpatrick, Laura; Waters, Janet; O'Neal, Mary Angela (Seminars in Neurology, 2022)
Women's neurology is the subspecialty within neurology concerned with the distinct healthcare needs of women. In this article, we review current literature and expert management strategies regarding disease-specific neurologic concerns of women, with an emphasis on issues related to contraception, pregnancy, and lactation. Health conditions that we discuss in this article include epilepsy, headache, stroke, multiple sclerosis, and Chiari I malformation. Current findings on neurologic disease in women suggest that many women with neurologic disease can safely manage their disease during pregnancy and have healthy children, though pregnancy planning is important in many conditions to mitigate risks and effective contraceptive management is important when pregnancy prevention is desired.
Keywords: women's neurology; pregnancy; contraception; breastfeeding; preeclampsia